STUDENT TEACHERS’ PERCEPTIONS OF REFLECTIVE PRACTICE - Seitova, Meruyert (International Online Journal of Education and Teaching, 2019)
The present study aims at engaging ELT student teachers in reflective teaching practice through the use of reflective diary during their school internship and finding out their perceptions about this reflective teaching practice that they were engaged in. The data were collected through the qualitative research instrument. After the student teachers were involved in reflective practice through the reflective tool, they were asked to keep reflective diaries during the twelve weeks school internship to learn their perceptions of reflective practice. The data obtained from the qualitative data were analyzed through thematic analysis. The results of the study put forward that the student teachers benefited much from the current study and were pleased with having participated in this reflective teaching practice by means of reflective diary. Engaging in reflective practice was found as an important opportunity for gaining awareness about teaching skills and practices, increasing self-evaluation and professional growth. The student teachers also stated that reflective diary use fostered the growth of reflective practice by encouraging them to engage in examining what was being done in the classroom. This process persuaded the individual to look for strengths and weaknesses and thus actively seek improvement in recognized areas. Though the growth of reflection and reflective practice, the student teachers used personal experiences and connection with classroom theory to grow and develop as professionals Keywords: Reflective teaching, reflective diary, self-evaluation, professional development.